2015
DOI: 10.1159/000440968
|View full text |Cite
|
Sign up to set email alerts
|

Administration of Ferric Citrate Hydrate Decreases Circulating FGF23 Levels Independently of Serum Phosphate Levels in Hemodialysis Patients with Iron Deficiency

Abstract: rum ferritin levels increased from 25.6 ± 24.3 ng/ml at baseline to 55.8 ± 33.5 ng/ml at 12 weeks with FCH administration. Serum intact FGF23 and C-term FGF23 levels significantly decreased at 12 weeks compared with baseline (2,000 (1,300.0-3,471.4) to 1,771.4 (1,142.9-2,342.9) pg/ml, p = 0.01, and 1,608.7 (634.8-2,308.7) to 1,165.2 (626.1-1,547.8) RU/ml, p = 0.007, respectively); serum intact PTH levels significantly increased (96 (65-125) to 173 (114-283) pg/ml, p < 0.001). Conclusions: Oral FCH administrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 32 publications
2
32
2
Order By: Relevance
“…In the present study, however, we could not evaluate whether ferric citrate modulated FGF23 degradation because C-terminal FGF23 levels were not measured. However, it has been reported that the ratio of intact to C-terminal FGF23, which indicates the amount of degradation of full-length FGF23, did not change following ferric citrate administration in hemodialysis patients, suggesting that ferric citrate has a relatively small influence on FGF23 degradation [16]. In the present study, switching from lanthanum carbonate to ferric citrate hydrate reduced FGF23 levels in patients on hemodialysis.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…In the present study, however, we could not evaluate whether ferric citrate modulated FGF23 degradation because C-terminal FGF23 levels were not measured. However, it has been reported that the ratio of intact to C-terminal FGF23, which indicates the amount of degradation of full-length FGF23, did not change following ferric citrate administration in hemodialysis patients, suggesting that ferric citrate has a relatively small influence on FGF23 degradation [16]. In the present study, switching from lanthanum carbonate to ferric citrate hydrate reduced FGF23 levels in patients on hemodialysis.…”
Section: Discussioncontrasting
confidence: 57%
“…Moreover, intravenous saccharated ferric oxide induced further increase in elevated FGF23 levels in hemodialysis patients [31]. Conversely, oral ferric citrate administration decreased serum intact FGF23 levels and increased iPTH levels in both hemodialysis-dependent and non-hemodialysis-dependent CKD patients [10, 16]. Furthermore, a study by David et al [34] on the chronic effects of iron supplementation showed that the role of iron on the degradation of circulating FGF23 might differ between the acute and the chronic phase of iron-deficiency anemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[153] circulating FGF23 levels independently of serum phosphate concentrations in hemodialysis patients [154]. In concert, an appropriate level of iron status is required to suppress serum FGF23 levels and potentially to prevent the development of cardiac hypertrophy.…”
Section: Non-iron Depleted Uremic Ratsmentioning
confidence: 99%
“…It is used to replete iron stores in iron deficiency anemia and reduces the requirement of intravenous iron and erythropoiesis stimulating agents (ESA) [4] and thus, ferric citrate is a dual-purpose therapeutic agent for dialysis patients. Recent studies reported that administration of ferric citrate led to decreased levels of serum fibroblast growth factor 23 (FGF23) independent of phosphate [3,5], reduced the cost of anemia-management therapies [6], and was associated with fewer hospitalizations and associated costs [7].…”
Section: Introductionmentioning
confidence: 99%